Changes in Serum Prostate-Specific Antigen Level after Prostatectomy in Patients with Benign Prostatic Hyperplasia - Hosseini, Seyed Yousef; Salimi, Mohammadreza; Hosseini Moghaddam, Seyyed Mohammad Mehdi (Urology Journal, 2009)
Introduction: The goal of this study was to investigate the effect of transurethral resection of the prostate and open prostatectomy on the serum prostate-specific antigen (PSA) level in men with benign prostatic hyperplasia. Materials and Methods: Serum prostate-specific antigen levels were determined before and 6 months after operation in 86 patients with benign prostatic hyperplasia who had undergone transurethral resection of the prostate or open prostatectomy. We measured the prostate volume by means of transrectal ultrasonography and weighed the surgical specimen. Changes in serum PSA levels and their correlation with prostate volume and the resected prostate weight were evaluated. Results: Of 86 patients, 45 underwent transurethral resection of the prostate and 41 underwent open prostatectomy. Mean PSA levels were reduced by 67.4 % (range, 0.40 ng/mL to 7.60 ng/mL) in the patients who had undergone transurethral resection of the prostate and 80.7% (range, 1.00 ng/mL to 14.50 ng/mL) in the patients with open prostatectomy. Removal of 1g of prostate tissue reduced serum PSA levels by an average of 0.15 ng/mL in those who underwent transurethral resection of the prostate and 0.10 ng/mL in those treated with open prostatectomy (P = .018). Forty patients (88.9%) in the group who underwent transurethral resection of the prostate and 39 (95.1%) in the open prostatectomy group exhibited a postoperative PSA level of less than 2.00 ng/mL (P = .20). Conclusion: A modified reference range seems necessary for the screening of prostate cancer via PSA level in men who have undergone prostatectomy for benign prostatic hyperplasia.